Learning about meaning making in museums - Miklošević, Željka (Array, 2012)
The aim of the paper is to explore the process of meaning construction in the contexts of museum representation and museum education. In addition to scientific and cultural information contained in and represented as artefacts, mentifacts and sociofacts, museums convey another sort of information in the process of meaning construction - "museological" information which are borne out of the institutional logic of meaning making, in other words, the ways the very institution creates multiple interpretations.